Bone health status, muscular performance, aerobic and anaerobic capacities of Malaysian young male state level weightlifting, cycling and squash athletes - Samsudin, Norsuriani (2018)
This study was carried out to determine the differences in bone health status, muscular performance, aerobic and anaerobic capacities of Malaysian young male state level weightlifting, cycling and squash athletes. Forty four participants (mean age: 17.1 ± 1.6 years old) were divided into sedentary control, weightlifting, cycling and squash groups with 11 participant for each group. Participants’ tibial and radial bone speed of sound (SOS) of dominant and non-dominant arms and legs were measured. In addition, participants’ isokinetic muscular strength and power, hand grip strength, back and leg strength, estimated maximal oxygen uptake (VO2max), and Wingate anaerobic capacities were determined. One way ANOVA was performed for statistical analysis. The present study found that weightlifting, cycling and squash athletes exhibited significantly greater tibial and radial bone SOS (p<0.01) compared to the sedentary control group. Bone SOS of the arm was highest in weightlifting athletes. Meanwhile, bone SOS of the leg was highest in cycling athletes. Weightlifting athletes showed significantly higher values of isokinetic knee extension, shoulder extension and shoulder flexion peak torque (strength) and average power (p<0.05) than cycling and squash athletes. Weightlifting athletes also showed significantly greater hand grip strength (p< 0.001), as well as back and leg strength (p< 0.001) compared to cycling and squash athletes. Cycling and squash athletes showed significantly higher aerobic capacity, i.e. estimated VO2max (p<0.001) compared to weightlifting and squash athletes. Weightlifting athletes exhibited significantly greater peak power (p< 0.05) than cycling and squash athletes. Besides, cycling athletes showed significantly higher anaerobic capacity and power (p< 0.001), and significantly lower fatigue index (p< 0.05) than weightlifting and squash athletes. Weightlifting and cycling athletes showed significantly shorter time to reach peak power (p< 0.01) than squash athletes. The present study findings implying that bone health status and physiological profiles of the athletes are dependent on sport events they were involved in. It is hoped that the results of the present study can be applied and help to facilitate the development of specific training programmes for achieving optimal performance of weightlifting, cycling and squash athletes, as well as promoting healthy lifestyle by engaging in sports like weightlifting, cycling and squash sports.